2021
DOI: 10.1039/d1an01708j
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering (SERS) spectroscopy on localized silver nanoparticle-decorated porous silicon substrate

Abstract: We use a simple, low-cost electroless etching and deposition process to create a localized silver nanoparticle decorated surface porous silicon (LocAg-PS). The LocAg-PS surface exhibits self-align and sample condensation capabilities for SERS analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Compared with the two-dimensional counterpart, three-dimensional SERS substrates can provide larger surface area, more hotspots in the excitation light beam, and thus higher sensitivity ( Li et al, 2018 ; Pal et al, 2019 ; Tsao et al, 2021 ). Therefore, three-dimensional nanoporous Al-Ag zig-zag silver nanorod arrays and buckled PDMS silver nanorod arrays fabricated by glancing angle deposition (GLAD), and three-dimensional hybrid MoS 2 /AgNPs/inverted pyramid PMMA resonant cavity system have shown excellent SERS performance ( Kumar et al, 2015 ; Rajput et al, 2017 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the two-dimensional counterpart, three-dimensional SERS substrates can provide larger surface area, more hotspots in the excitation light beam, and thus higher sensitivity ( Li et al, 2018 ; Pal et al, 2019 ; Tsao et al, 2021 ). Therefore, three-dimensional nanoporous Al-Ag zig-zag silver nanorod arrays and buckled PDMS silver nanorod arrays fabricated by glancing angle deposition (GLAD), and three-dimensional hybrid MoS 2 /AgNPs/inverted pyramid PMMA resonant cavity system have shown excellent SERS performance ( Kumar et al, 2015 ; Rajput et al, 2017 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Concerning the use of metals, nanostructured silver (Ag) is of particular interest due to its versatile usage. The optoelectronic properties of Ag on the nanoscale can be exploited in catalysts, 24,25 flexible electrodes, 26 sensors, [27][28][29][30][31][32][33] photonic crystals 34,35 and antibacterial agents. 36,37 Furthermore, it was previously shown that a thin polymer film can be stabilized by the presence of noble metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…There are several papers that have shown the improvement in SERS enhancement, introducing several techniques such as the combination of metal-organic frameworks (MOFs) with plasmonic metal nanoparticles [34], silver nanoparticles with porous silicon substrate [35], metal-modified montmorillonite [36], AuNRs functionalized zirconiumbased MOFs [37], and etched-spiky Au@Ag plasmonic superstructures [38]. Our system can analyze bacteria samples without labels using a reusable biosensing device made of graphene and AuNRs.…”
Section: Introductionmentioning
confidence: 99%